Experimental Analysis Of Vapour Compression Refrigeration System For Optimum Performance With Low Pressure Receiver - G. Maruthi Prasad Yadav, R.Vasanthi, (International Journal of Scientific Research and Management (IJSRM), 2015)
Refrigerator is a device used for chilling of food products for the both commercial and domestic appliances utilizing mechanical vapour compression Cycle in its process. Optimization for the better performance of the system becomes main issue and many researches are still ongoing to improve efficiency of the system. The main objective of this work is to enhance the performance of the domestic refrigerator by flooding the evaporator with liquid refrigerant. To attain this objective a low pressure vessel is designed, developed, fabricated and incorporated between evaporator and compressor. The performance of refrigerator is evaluated with and without low pressure receiver. Also analysis is carried using two different refrigerants (R134a and R401C). From the results it is found that COP, refrigeration of the system improves with the installation of low pressure receiver. Also the system gets benefited in the form of decrease in compressor work with the installation of low pressure receiver. Comparing the performance parameters of the refrigeration system with different refrigerants it is found that R401C gives optimum performance over the R134A.